Assessment of relationship between doctor and patient in a selected Hospital: Patient’s perspective - Nessa, Maharun; Sultana, Shuhana; Hossain, Sharmin (Utan Kayu Publishing, 2025)
The doctor-patient relationship is a fundamental element of medical practice that plays a crucial role in determining patient satisfaction and health outcomes. In developing countries like Bangladesh, where the healthcare system faces various challenges, understanding the doctor-patient dynamic becomes even more critical. This study aimed to assess the relationship between doctors and patients from the patients' perspective in a selected hospital in Bangladesh. A descriptive cross-sectional survey was conducted over a one-year period with 422 participants aged 18 years and above. Data were collected through a self-administered questionnaire focusing on patients' perceptions of doctors' attentiveness, consultation time, clarity of medical explanations, and satisfaction with consultation fees. The findings revealed that 71.09% of patients perceived doctors as cordial, while 83.18% felt that doctors provided adequate consultation time. However, only 38.66% believed they received sufficient mental support from doctors, and a significant proportion of patients struggled to understand the prescribed medication and advice. Additionally, satisfaction with consultation fees was notably low, with only 23.70% of participants expressing positive feedback. These results highlight the need for improved communication and emotional support in doctor-patient interactions. Addressing these gaps could significantly enhance the overall quality of healthcare services in Bangladesh. The study provides valuable insights into the socio-economic factors influencing patient perceptions and emphasizes the importance of strengthening the doctor-patient relationship to improve healthcare outcomes. Future research should focus on broader samples across multiple institutions to obtain a more comprehensive understanding of this dynamic.